Influence of sustainable production on sustainable performance of small and medium enterprises in the Malaysian manufacturing industry - Abbass, Nazik Mahmoud (2018)
Industrialisation has played a significant role in the nation’s development. However, in the 20th century, this development was focused mainly on economic growth. Two decades ago, The United Nation raised the issue of merging environmental and social aspects to economic development to mitigate the negative environmental and social impacts of production and consumption. Anchored on the Natural Resource-Based View, implementation of Sustainable production through all process life cycle undertaken as a firms’ resource to achieve the sustainable performance, which comprises the environmental pillar, social pillar, and financial pillar will be a competitive advantage and reflect the holistic form of sustainability. In Malaysia context, sustainable production is in an early stage. The general objective is to investigate the factors that influence the implementation of sustainable production through all process life cycle, and its influence on small and medium enterprises (SMEs) sustainable performance encompass the three pillars in Malaysia manufacturing industry. The study employed a self-administered close-ended survey questionnaire for data collection. The survey questionnaire was distributed to the senior managers of manufacturing SMEs in Malaysia, based on the Federation of Malaysia Manufacturers directory (46th edition, 2015). 185 questionnaires were collected as a sample size. The hypotheses examined relationships between stakeholders and top management and sustainable production elements, and sustainable production and SMEs sustainable performance dimensions. Besides, the moderation effect of the company size on the relationship between the sustainable production and sustainable performance dimensions were tested. The study employed smart-PLS3 software. The response rate for the research was within acceptable range in the Malaysian context. The study found that government, shareholders/owners, and top management but not the customers, influence sustainable production. Consequently, sustainable production positively influenced manufacturing SMEs’ sustainable performance. On the other hand, the company size positively moderates the relationship of sustainable production and sustainable performance collectively and individually except for the social value. The academic and practical contribution of the study that sustainable practice in its holistic form will results in better performance, hence, for stakeholder, implementation of sustainable production through all process life cycle as useful resource is the right solution for manufacturing SMEs to acquire proper sustainable performance as a competitive advantage. Besides, SMEs required enhancing their access to higher financial and human resource to achieve higher sustainable performance. Findings of the study should support scholars, governments, and decision-makers to understand the theoretical and practical implications of integrating sustainable production through the whole life cycle. The research framework is developed to propose a set of sustainable production indicators for manufacturing SMEs in Malaysia SMEs, in order to assist the government and decision-makers to support manufacturing SMEs in the implementation the policy of sustainable practice. SMEs required both technical and financial support to improve their resource and capabilities.